Neutrosophic Components Structure Semigroups for Risk Evaluation of Financial Archive Management in Small and Medium-Sized Enterprises - Zhongyin Dong; Pei Wan (Neutrosophic Sets and Systems)
Small and medium-sized businesses (SMEs) are finding it more and more difficult to safely and efficiently manage financial archives in the digital era. The dangers related to the storage, access, and compliance of financial data are increased with greater dependence on digital platforms. The risk assessment of financial archive management systems in SMEs is examined in this study, with a focus on the complexity of operational, legal, cybersecurity, and technology concerns. This research gives SMEs an organized way to make well-informed decisions by establishing important risk factors and evaluating various archive management options, from manual methods to cloud and blockchain-based platforms. To reflect the ambiguity and uncertainty present in real-world risk assessment, the study employs a neutrosophic component semigroup structure framework backed by neutrosophic logic. This study shows definitions of neutrosophic component structure semigroup with set of examples. Case study with five criteria and four alternatives is provided to show the validation of operations of neutrosophic framework.